2020
DOI: 10.1371/journal.pone.0228659
|View full text |Cite
|
Sign up to set email alerts
|

Urbanicity, biological stress system functioning and mental health in adolescents

Abstract: Growing up in an urban area has been associated with an increased chance of mental health problems in adults, but less is known about this association in adolescents. We examined whether current urbanicity was associated with mental health problems directly and indirectly via biological stress system functioning. Participants (n = 323) were adolescents from the Dutch general population. Measures included home and laboratory assessments of autonomic nervous system and hypothalamic-pituitary-adrenal axis functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 96 publications
0
14
1
1
Order By: Relevance
“…These results are also consistent with previous research. A harmonious family atmosphere is related to good mental health [ 39 , 40 ], while a lack of family recreational activities and poorer communication reduces mental health [ 41 ]. Less strict parental control also improves adolescent mental health [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are also consistent with previous research. A harmonious family atmosphere is related to good mental health [ 39 , 40 ], while a lack of family recreational activities and poorer communication reduces mental health [ 41 ]. Less strict parental control also improves adolescent mental health [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, urbanization is one of the dominant demographic trends in the 21 st century ( 22 ). Importantly, living in an urban area seems to be associated with an increased risk of mental health problems, compared to living in a rural area ( 19 ). Retrospective studies showed that this increased risk for mental health problems in adults may be greater for those who grew up in an urban context ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Flemish study, tracking 175 children during a 3-year time period between childhood and adolescence, found that higher residential exposure to semi-natural and forested areas was associated with increased feelings of happiness, while a poorer emotional status was seen with increased residential traffic exposure ( 56 ). Chronic stress through HPA axis activation has been suggested as a potential biological mechanism, underlying the association between urbanicity and health ( 19 ). In our adolescent study population, household SES and neighborhood SES were not associated with HCC, nor was psychosocial stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations